2022
DOI: 10.3390/microorganisms10091735
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Iron Limitation, Elevated Temperature, and Florfenicol on the Proteome and Vesiculation of the Fish Pathogen Aeromonas salmonicida

Abstract: We analyzed the proteomic response of the Gram-negative fish pathogen A. salmonicida to iron limitation, an elevated incubation temperature, and the antibiotic florfenicol. Proteins from different subcellular fractions (cytosol, inner membrane, outer membrane, extracellular and outer membrane vesicles) were enriched and analyzed. We identified several iron-regulated proteins that were not reported in the literature for A. salmonicida before. We could also show that hemolysin, an oxidative-stress-resistance cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 83 publications
0
5
0
Order By: Relevance
“…T2SS functions as a transport mechanism to translocate proteins (such as aerolysin, proteases, DNases and amylases) from the periplasm to the extracellular environment in Aeromonas (Li et al, 2011; Seshadri et al, 2006), and the ExeAB homologue GspAB complex has been demonstrated to be functional in the assembly of the T2SS secretin multimer in A. salmonicida (Strozen et al, 2011). The haemolytic genes aerA and hlyA have been found to be significantly up‐regulated in mesophilic A. salmonicida SRW‐OG1 grown at 28 and 37°C compared to 18°C (Chen et al, 2022), and the haemolytic activity of A. salmonicida is enhanced by elevated incubation temperature or limited iron (Chen et al, 2022; Kroniger et al, 2022). It can be thought that these common virulence factors constitute the basic virulence of A. salmonicida .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…T2SS functions as a transport mechanism to translocate proteins (such as aerolysin, proteases, DNases and amylases) from the periplasm to the extracellular environment in Aeromonas (Li et al, 2011; Seshadri et al, 2006), and the ExeAB homologue GspAB complex has been demonstrated to be functional in the assembly of the T2SS secretin multimer in A. salmonicida (Strozen et al, 2011). The haemolytic genes aerA and hlyA have been found to be significantly up‐regulated in mesophilic A. salmonicida SRW‐OG1 grown at 28 and 37°C compared to 18°C (Chen et al, 2022), and the haemolytic activity of A. salmonicida is enhanced by elevated incubation temperature or limited iron (Chen et al, 2022; Kroniger et al, 2022). It can be thought that these common virulence factors constitute the basic virulence of A. salmonicida .…”
Section: Discussionmentioning
confidence: 99%
“…salmonicida is enhanced by elevated incubation temperature or limited iron (Chen et al, 2022;Kroniger et al, 2022). It can be thought that these common virulence factors constitute the basic virulence of A. salmonicida.…”
Section: F I G U R Ementioning
confidence: 99%
“…For other bacteria, the OMV secretion in environments with different iron availability was demonstrated mainly for iron starvation conditions. For example, Aeromonas salmonicida , Haemophilus influenzae , Vibrio cholerae , Helicobacter pylori , Escherichia coli, and Mycobacterium tuberculosis produce OMVs in iron starvation conditions 7 , 28 31 . Data on OMVs released by bacteria in iron repletion conditions are minimal.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies further showed that iron limitation leads to the activation of numerous virulence genes in many pathogenic bacteria, including N. meningitidis [ 46 ]. In addition, the results of investigations on Aeromonas salmonicida suggest that OMVs produced from limited-iron stressed bacteria are involved in iron acquisition and may be suitable for inducing protective immune responses [ 47 ].…”
Section: Discussionmentioning
confidence: 99%